Increased Survival in B-Cell-Deficient Mice during Experimental Cerebral Malaria Suggests a Role for Circulating Immune Complexes - Rosane B. de Oliveira (American Society for Microbiology, 2014)
ABSTRACT The pathogenesis of malaria, an insect-borne disease that takes millions of lives every year, is still not fully understood. Complement receptor 1 (CR1) has been described as a receptor for Plasmodium falciparum, which causes cerebral malaria in humans. We investigated the role of CR1 in an experimental model of cerebral malaria. Transgenic mice expressing human CR1 (hCR1+) on erythrocytes were infected with Plasmodium berghei ANKA and developed cerebral malaria. No difference in survival was observed in hCR1+ mice compared to wild-type mice following infection with P. berghei ANKA; however, hCR1 detection was significantly diminished on erythrocytes between days 7 and 10 postinfection. hCR1 levels returned to baseline by day 17 postinfection in surviving animals. Immunoblot assays revealed that total erythrocyte hCR1 levels were diminished, confirming that immune complexes in association with erythrocyte hCR1 were likely removed from erythrocytes in vivo by clearance following immune adherence. Decreases in hCR1 were completely dependent on C3 expression, as mice treated with cobra venom factor (which consumes and depletes C3) retained hCR1 on erythrocytes during C3 depletion through day 7; erythrocyte hCR1 decreases were observed only when C3 levels recovered on day 9. B-cell-deficient mice exhibit a marked increase in survival following infection with P. berghei ANKA, which suggests that immune complexes play a central role in the pathogenesis of experimental cerebral malaria. Together, our findings highlight the importance of complement and immune complexes in experimental cerebral malaria. IMPORTANCE Cerebral malaria is a deadly complication of infection with Plasmodium falciparum. Despite its high prevalence, relatively little is understood about its pathogenesis. We have determined that immune complexes are generated and deposited on erythrocytes specifically expressing human complement receptor 1 in a mouse model of cerebral malaria. We also provide evidence demonstrating the importance of immunoglobulins in the pathogenesis of cerebral malaria in mice. These findings may have important implications in human cerebral malaria.